Indigenous leadership and mass media. The case of Alberto Pizango in Peruvian politics - Romio, Silvia (2022)
Over the last fifty years, indigenous leadership has undergone a series of important transformations. This trajectory has been dominated by a process of merging and reworking different models of leadership fromlocal, national and global contexts. In all of this, the creative use of visual tools and mass media has played a fundamental role. Within the Peruvian political scenario, the figure of Alberto Pizango Chota, Shawi leader ofthe Aidesep organisation, has set an important precedent in this regard. His case is an exemplary field of study on the extraordinary possibilities of exhibition, the use of images, the fabrication of aesthetics and the elaboration of new expressive codes. These are all elements that contemporary Amazonian leadership can propose and disseminate through digital technologies and relations with the mass media.